Structuring Uncertainties in Long-Range Power Planning - Motlagh, Cyrus K. (East Lansing: Division of Research, Graduate School of Business Administration, Michigan State University, 1976)
The author describes extensively, electrical power planning; electrical demand forecasts and their use; simulated expansion of generation capability; economic analysis in simulated expansion of a generating system; and further interprets the results.
Includes bibliographical references: p. 165-167.
ne 27/04/2018
Loan
Keywords: Electric Utilities; Uncertainty